Factors Hindering Study Completion Among Islamic Economics Undergraduate Students at the State Islamic University of Sunan Ampel Surabaya - Wigati, Sri; Hasan, Nurul Fatma (JURNAL JENDELA PENDIDIKAN, 2025)
This study aims to analyze the factors that hinder on-time graduation (OTG) among students of the Islamic Economics Program at the Faculty of Economics and Islamic Business, UIN Sunan Ampel Surabaya. The research employs a descriptive quantitative method with a survey approach. The sample consists of non-OTG students who have studied for more than eight semesters. Data were collected through a Likert-scale questionnaire encompassing six factors of on-time graduation: motivation, environment, activities, supervisory support, academic proficiency, and economic conditions. The results indicate that based on the average weight, the factors influencing on-time graduation of Islamic Economics students at UIN Sunan Ampel Surabaya are, in order, activities, academic proficiency, motivation, supervisory involvement, environment, and economic factors. The activities factor is the only one agreed upon by respondents as the dominant factor, with the primary cause of delayed graduation being the high level of student involvement in activities outside of their studies. These findings have implications for program managers in enhancing academic services and guidance to promote timely graduation for students.